THE BOY, HIS TEACHER AND THE LINGUIST: LEARNING TURKISH WITH AESOP FABLES - Safir, Kassim Boudjelal (IJIET (International Journal of Indonesian Education and Teaching), 2025)
Can we Aesopianise other languages? This is what this article is about. You must be familiar with the fable of the Fox and the Grapes. Arent you? Its popularity has crossed the borders and became one of the most shared fables in the world. That popularity (1) is in fact an asset for linguists to implement the linguistic context predictability (2) using narratives. On the other hand, borrowings (3) and collocational patterns (4) can be of paramount importance to unlocking linguistically related languages. Therefore, it would be interesting to approach fables through specific strategies to try to guess familiar texts in context. To test this novel approach, we invited ten master students to participate in an experiment where they were asked to perform a series of tasks using the four linguistic tools in a game-like exercise. The results showed that participants succeeded in the post-test 26.09% of the lexicon found in ten popular fables -which is for sure not excellent but highly encouraging- when compared with that little 2.94% in the pre-test. Furthermore, the study implies that linguistic awareness preceded by cultural awareness could be a significantly powerful tool for learning any foreign language.